Classification Analysis of Unilak Informatics Engineering Students Using Support Vector Machine (SVM), Iterative Dichotomiser 3 (ID3), Random Forest and K-Nearest Neighbors (KNN) - Sunaryanto, Hadi; Hasan, Mhd Arief; Guntoro, Guntoro (UIR PRESS, 2022)
This research is entitled “Classification Analysis of the Study Period of Informatics Engineering Study Program Students at Unilak with the Support Vector Machine (SVM), Iterative Dichotomiser 3 (ID3), Random Forest and K-Nearest Neighbors (KNN)